Enzymatic versus Electrocatalytic Oxidation of NADH at Carbon‐Nanotube Electrodes Modified with Glucose Dehydrogenases: Application in a Bucky‐Paper‐Based Glucose Enzymatic Fuel Cell. Issue 12 (16th November 2016) - Lalaoui, Noémie; Means, Nicolas; Walgama, Charuksha; Le Goff, Alan; Holzinger, Michael; Krishnan, Sadagopan; Cosnier, Serge
Abstract: In this work, we have designed and compared functionalized carbon‐nanotube‐based electrodes for the electrocatalytic oxidation of NADH. We show that oxidation of NADH at neutral pH values can be performed by pristine multi‐walled carbon nanotubes (MWCNT) and directly wired diaphorase or ruthenium phenanthrolinequinone molecular catalysts. Glucose dehydrogenase was immobilized on these MWCNT electrodes by an activated‐ester‐modified pyrene linker. Glucose‐oxidizing bioelectrodes were compared and integrated into a bucky‐paper‐based glucose/O2 biofuel cell, using a bilirubin‐oxidase‐modified bucky‐paper cathode. The best configuration was obtained using a NADH‐oxidizing molecular catalyst at the anode. The biofuel cell exhibits an open‐circuit voltage of 0.62 V and delivers a power output of 0.47 mW cm −2 . Abstract : Tried and tested : A series of carbon‐nanotube‐based electrodes for the electrocatalytic oxidation of NADH was designed and tested. Glucose dehydrogenase (GDH) was immobilized on the electrodes which were subsequently integrated into a bucky‐paper‐based glucose/O2 biofuel cell using a bucky‐paper (BP) cathode modified with bilirubin oxidase (BOD).